2019
DOI: 10.1186/s13031-019-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of posttraumatic growth among conflict-related sexual violence survivors from Bosnia and Herzegovina

Abstract: Background Conflict-related sexual violence (CRSV) was committed on a large scale against women across Bosnia and Herzegovina (BiH) during the 1990’s war, and research has shown both negative and positive psychosocial outcomes following such acts of interpersonal violence. We aim to determine the capacity for posttraumatic growth (PTG) among a population of women who experienced CRSV, and to what extent it is impacted by factors such as coping and optimism. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…The sample sizes of studies ranged from 2 to 39,703 with 19 (48.8%) studies having used qualitative, 19 (46.3%) quantitative, and 3 (7.3%) mixed-methods. The vast majority (63.4%) of studies were conducted in the USA (Cole and Lynn, 2010;Singh et al, 2010;Drauker et al, 2011;Warner Stidham et al, 2012;Williams and Nelson-Gardell, 2012;Wilson et al, 2012;Arias and Johnson, 2013;Davidson et al, 2013;McClain and Frederick Amar, 2013;Foster and Hagedorn, 2014;Ullman, 2014;Bryant-Davis et al, 2015;Kelley and Gidycz, 2015;Simon et al, 2015;Crews et al, 2016;Hartley et al, 2016;Hitter et al, 2017;Kerlin and Sosin, 2017;Smigelsky et al, 2017;Barnett and Maciel, 2019;Catabay et al, 2019;Kirkner and Ullman, 2019;Lahav et al, 2019;Nelson et al, 2019;Saint Arnault and Sinko, 2019;Strauss Swanson and Szymanski, 2020) followed by European studies with 9.8% (Phanichrat and Townshend, 2010;Whitelock et al, 2013;Perez-Gonzalez et al, 2017;Anderson et al, 2019), and two in South Africa (Phasha, 2010;Walker-Williams et al, 2012). One study each was from Australia (Vilencia et al, 2013), Bangladesh (Kaiser and Sinanan, 2020), Brazil (Pessoa et al, 2017), India (George and Bance, 2019), Israel (Kaye-Tzadok and Davidson-Ard, 2016),...…”
Section: Findings General Study Characteristicsmentioning
confidence: 99%
“…The sample sizes of studies ranged from 2 to 39,703 with 19 (48.8%) studies having used qualitative, 19 (46.3%) quantitative, and 3 (7.3%) mixed-methods. The vast majority (63.4%) of studies were conducted in the USA (Cole and Lynn, 2010;Singh et al, 2010;Drauker et al, 2011;Warner Stidham et al, 2012;Williams and Nelson-Gardell, 2012;Wilson et al, 2012;Arias and Johnson, 2013;Davidson et al, 2013;McClain and Frederick Amar, 2013;Foster and Hagedorn, 2014;Ullman, 2014;Bryant-Davis et al, 2015;Kelley and Gidycz, 2015;Simon et al, 2015;Crews et al, 2016;Hartley et al, 2016;Hitter et al, 2017;Kerlin and Sosin, 2017;Smigelsky et al, 2017;Barnett and Maciel, 2019;Catabay et al, 2019;Kirkner and Ullman, 2019;Lahav et al, 2019;Nelson et al, 2019;Saint Arnault and Sinko, 2019;Strauss Swanson and Szymanski, 2020) followed by European studies with 9.8% (Phanichrat and Townshend, 2010;Whitelock et al, 2013;Perez-Gonzalez et al, 2017;Anderson et al, 2019), and two in South Africa (Phasha, 2010;Walker-Williams et al, 2012). One study each was from Australia (Vilencia et al, 2013), Bangladesh (Kaiser and Sinanan, 2020), Brazil (Pessoa et al, 2017), India (George and Bance, 2019), Israel (Kaye-Tzadok and Davidson-Ard, 2016),...…”
Section: Findings General Study Characteristicsmentioning
confidence: 99%
“…In a previous study based on the dataset presented in this article (Anderson et al, 2019) findings from women in Bosnia & Herzegovina who experienced CRSV during the war from 1992-1995, showed that higher levels of positive reinterpretation (as a form of approach coping; i.e. seeing a situation in a favourable light) and lower levels of behavioural disengagement (as a form of avoidance coping; i.e.…”
Section: Introductionmentioning
confidence: 75%
“…Subscales are calculated using the mean score of items. Based on results from prior research (Anderson et al, 2019) two subscales were used in this study: 'positive reinterpretation' is comprised of 4 items (e.g. "I try to make it seem more positive"), and behavioural disengagement is comprised of 5 (e.g."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the literature outlined above (Brooks et al, 2018;Elderton et al, 2017;Kuwert et al, 2014), and the findings of our previous study (Anderson et al, 2019) a model of PTG was defined. The 6 core assumption is that the relationship between CRSV and PTG is mediated by psychosocial factors such as coping.…”
Section: Introductionmentioning
confidence: 99%